2019
DOI: 10.3390/cancers11121957
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer Dissemination—A Cell Biologist’s Perspective

Abstract: Epithelial ovarian cancer (EOC) comprises multiple disease states representing a variety of distinct tumors that, irrespective of tissue of origin, genetic aberrations and pathological features, share common patterns of dissemination to the peritoneal cavity. EOC peritoneal dissemination is a stepwise process that includes the formation of malignant outgrowths that detach and establish widespread peritoneal metastases through adhesion to serosal membranes. The cell biology associated with outgrowth formation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 165 publications
(202 reference statements)
0
18
0
Order By: Relevance
“…Peritoneal dissemination is the most common mechanism of disease progression in ovarian cancer [178]. It is associated with the development of malignant ascites, which is a major cause of chemoresistance and recurrence.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Peritoneal dissemination is the most common mechanism of disease progression in ovarian cancer [178]. It is associated with the development of malignant ascites, which is a major cause of chemoresistance and recurrence.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…On the other hand, FN1 might also constitute an extracellular substrate for ovarian cancer cell aggregation in spheroids in the absence of stromal fibroblasts. It had been previously demonstrated that soluble ECM proteins, such as FN1 and vitronectin are detectable in ascitic fluid [ 28 ] and are organized by integrins for survival and proliferation (for a review see [ 44 ]). The role of endogenous FN1 in metastasis has been previously demonstrated in experimental models of ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of these activities is unknown. Promising candidates of non-AKT signals include soluble ECM proteins, such as laminin, fibronectin in FF [ 56 ] in promoting the adhesion, spreading, and migration of tumor cells via FAK [ 16 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, exfoliated STIC cells are frequently found in the lumen of the fallopian tube [ 15 ]. This demonstrates the following model of STIC metastasis: a long-term, constant shedding of STIC cells into the peritoneal cavity, which leads to anoikis until tumor cells have evolved to survive, ability of attachment and growth in the new microenvironment on the peritoneal or ovarian surface, and invasion into the underlying stroma to establish metastasis [ 16 ]. This characteristic shedding-and-seeding mechanism of STIC metastasis differs much from the classical invasion-and-intravasation mechanism of other in situ carcinomas, and this will be a focus of our study.…”
Section: Introductionmentioning
confidence: 99%